Early spring egg hatching by the American lobster (Homarus americanus) linked to rising water temperature in autumn. (13th March 2020) - Haarr, Marthe Larsen; Comeau, Michel; Chassé, Jöel; Rochette, Rémy
Abstract: Increasing ocean temperatures may affect life cycles of organisms whose biological processes are temperature-dependent. Our objective was to determine whether hatching time of American lobster ( Homarus americanus ), which has a 2-year reproductive cycle, has advanced in the southern Gulf of St Lawrence, Canada, in response to rising temperature. We investigated temporal trends in hatching time 1989–2014 using fisheries monitoring data. We considered two metrics: the first week of the year when ovigerous females with prehatch or hatching clutches were observed [onset-of-hatching (OH)] and the rate of change in the ratio of females with prehatch/hatching vs. developing clutches each spring fishing season [rate of clutch development (RCD)]. OH advanced by 5 weeks and RCD increased by 40% on average. Comparisons of OH and RCD to cumulative degree-days going back 2 years prior to hatching suggested an effect of higher fall temperatures during early ovarian and embryonic development. The advancement of hatching time in response to environmental conditions 6–18 months before hatching occurs could lead to a mismatch with larval prey species with shorter life cycles. These findings highlight the importance of monitoring phenology of fished species and the need for further research into potential impacts of phenological changes.